Aramid nanofiber reinforced cable core tape material and preparation method thereof
By using aramid nanofiber reinforced material in the cable core tape wrap material, combined with mica scales and glass fiber cloth, the existing materials have been solved, and the existing materials have low temperature resistance and insufficient insulation performance have been achieved, and a high temperature resistance and high insulation cable core tape wrap material is achieved, meeting the high flame retardant and high fire resistance needs of high-end cables.
Patent Information
- Application Number
- CN202211599332.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-12
AI Technical Summary
The existing cable cable core strap materials have low temperature resistance, insufficient insulation performance and short service life, which cannot meet the high flame retardant and high fire protection needs of high-end cables in nuclear power, high-speed rail, aerospace and other fields.
The preparation method of aramid nanofiber reinforced cable core tape wrap material is adopted to prepare dark red aramid nanofiber dispersion liquid by reaction of high concentration alkali liquid, dimethyl sulfoxide and aramid fiber. Combining mica scales and glass fiber cloth, aramid nanofiber coating is used to replace traditional adhesives, and hot press bonding is performed.
The temperature resistance level of the cable core strap material is improved to C (above 180℃), the insulation performance and service life are enhanced, and the high flame retardant and high fireproof needs of high-end cables are met.
Smart Images

Figure CN115923210B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable core tape material preparation, and specifically relates to an aramid nanofiber reinforced cable core tape material and a preparation method thereof. Background Art
[0002] Mica powder has outstanding insulation, corona resistance, and heat resistance properties. It is an indispensable insulation and heat-resistant material for cable manufacturing. However, the interface effect of mica flakes is weak, and it has almost no strength after being made into paper. In order to solve this problem, the manufacturing of traditional cable core tape materials usually introduces adhesives such as silicone and PET base cloth for reinforcement and support. However, materials such as silicone (heat resistance of 115°C) and PET base tape (heat resistance of 160°C) have low temperature resistance grades, weak insulation strength, and are easy to age, resulting in reduced insulation, temperature resistance, and service life of the cable core tape materials. In addition, it is impossible to cooperate with functional coatings to meet the needs of high flame retardancy and high fire resistance, which hinders the development of high-end cables in my country's nuclear power, high-speed rail locomotives, aerospace, national defense and military industries. The existing commercially available cable core tape materials can no longer meet the actual needs of the world's nuclear power and high-speed rail processes for special cable manufacturing materials. Summary of the invention
[0003] Aiming at the problem that adhesive components limit the strength, temperature resistance level, insulation level and application life of cable core tape materials, the present invention provides an aramid nanofiber reinforced cable core tape material and a preparation method thereof.
[0004] The present invention is achieved through the following technical solutions:
[0005] A method for preparing an aramid nanofiber reinforced cable core tape material comprises the following steps:
[0006] Step 1, adding highly concentrated alkali solution, dimethyl sulfoxide and aramid fiber in sequence, and then sealing and stirring to react to prepare a dark red aramid nanofiber dispersion;
[0007] Step 2, adding deionized water to the aramid nanofiber dispersion to perform solvent stirring and replacement, and filtering to obtain an aramid nanofiber wet gel; then adding a polyvinyl alcohol solution to the aramid nanofiber wet gel to prepare an aramid nanofiber coating;
[0008] Step 3: Evenly mix the mica flakes and the aramid nanofiber coating, apply them by scraping to form an aramid mica thin layer, and dry them to obtain a dried aramid mica thin layer;
[0009] Step 4: Spray the aramid nanofiber coating on the surface of the glass fiber cloth, and then bring the surface coated with the aramid nanofiber into contact with the dried aramid mica thin layer for hot pressing and bonding to obtain the aramid nanofiber reinforced cable core tape material.
[0010] Preferably, in step 1, the aramid fiber is a para-aramid fiber with a para-structure of (1414), and the raw materials of the aramid fiber are para-aramid short chopped fibers, para-aramid fiber fabrics, para-aramid fiber scraps, and high-temperature resistant protective gear woven with para-aramid fibers.
[0011] Preferably, in step 1, the ratio of high-concentration alkali solution, dimethyl sulfoxide, and aramid fiber is (2-3) mL: (400-500) mL: (2-4) g, wherein the alkali solution is a combination or any one of potassium tert-butoxide, potassium hydroxide, and lithium hydroxide, with a concentration of (1.0-1.2) g / mL, the stirring reaction time is (24-48) h, and the rotation speed is (300-600) r / min.
[0012] Preferably, in step 2, the ratio of deionized water to aramid nanofiber dispersion is (100-200) mL: (600-800) mL, wherein the stirring time is (2-4) h, the rotation speed is (300-400) r / min, and a 2800 mesh filter is used for filtration and the filtration is allowed to stand for (3-5) h.
[0013] Preferably, in step 2, the polyvinyl alcohol solution is (5-10) g / L; the polyvinyl alcohol solution is added to the aramid nanofiber wet gel in a ratio of (5-10) mL: (20-30) g.
[0014] Preferably, in step 3, during mixing, the mica flakes and the aramid coating are mixed in a ratio of (85-95) g: (5-15) g, and the mixing is evenly stirred at a number of (10,000-20,000) revolutions.
[0015] Preferably, in step 3, the thickness of the aramid mica thin layer is (1-2) mm.
[0016] Preferably, in step 3, the drying temperature is (80-105)°C and the drying time is (10-20) min.
[0017] Preferably, in step 4, the spraying amount of the aramid nanofiber coating on the surface of the glass fiber cloth is (15-25) g / m 2 The temperature during hot pressing is (150-200)°C and the pressure is (5-10) MPa.
[0018] A cable core tape material prepared by a method for preparing an aramid nanofiber reinforced cable core tape material.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The invention discloses a method for preparing an aramid nanofiber reinforced cable core tape material, comprising the steps of alkaline hydrolysis of aramid fibers, solvent washing, displacement and separation, coating preparation and viscosity adjustment, aramid mica preform scraping and forming, vacuum drying, glass fiber cloth adhesive hot pressing and the like. While ensuring a high mica content, the process has the advantages of being green, low energy consumption, noiseless and highly efficient.
[0021] In view of the problems of low temperature resistance grade, limited insulation performance and short service life of traditional silicone adhesive cable core tape materials, the present invention replaces the silicone adhesive with aramid nanofiber coating, and adopts aramid nanofiber coating (heat resistant to 300°C, self-extinguishing) to replace the traditional cable core tape PET base tape and silicone to make an enhanced cable core tape material with a hierarchical structure, which solves the shortcomings of the existing commercially available cable core tape adhesives and makes the temperature resistance grade of the overall cable core tape material reach Class C (above 180°C).
[0022] The present invention provides a method for preparing an aramid nanofiber reinforced cable core tape material, which proposes the blending and bonding of mica flakes and aramid nanofibers and the spray bonding of glass fiber cloth, giving the present invention a higher feasibility in the actual engineering process and laying a foundation for mass production of products. In addition, the reagents used in the preparation are all conventional pharmaceutical reagents, which are low-toxic, cheap, and easy to obtain, and the equipment used are all conventional instruments and equipment, which lays a foundation for the marketization of the process technology products protected by the invention, reduces costs, and improves market competitiveness.
[0023] Furthermore, the selection of drying temperature range, gelation filter and the amount of viscosity regulator polyvinyl alcohol in the preparation process are all the results of long-term process optimization. The drying temperature shortens the preparation cycle to the greatest extent while saving energy. The gelation retains all the nanofibers while improving the efficiency. The polyvinyl alcohol adjusts the process without affecting the overall quality of the aramid nanofiber coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a schematic structural diagram of an aramid nanofiber reinforced cable core tape material. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0026] The present invention discloses a method for preparing an aramid nanofiber reinforced cable core tape material, comprising the following steps:
[0027] Step 1: Add highly concentrated alkali solution, dimethyl sulfoxide and aramid fiber into a stirrer in sequence, and seal and stir the mixture to prepare a dark red aramid nanofiber dispersion.
[0028] The aramid fiber is a para-aramid fiber with a para-structure of (1414), and the raw materials of the aramid fiber are para-aramid short cuts, para-aramid fiber fabrics, para-aramid fiber scraps, and high-temperature resistant protective gear woven with para-aramid fibers.
[0029] The ratio of high-concentration alkali solution, dimethyl sulfoxide and aramid fiber is (2-3) mL: (400-500) mL: (2-4) g, wherein the alkali solution is a combination or any one of potassium tert-butoxide, potassium hydroxide and lithium hydroxide, with a concentration of (1.0-1.2) g / mL, the stirring reaction time is (24-48) h, and the rotation speed is (300-600) r / min.
[0030] Step 2, adding deionized water to the aramid nanofiber dispersion to stir and replace the solvent, the ratio of deionized water to the aramid nanofiber dispersion is (100-200) mL: (600-800) mL, wherein the stirring time is (2-4) h, the rotation speed is (300-400) r / min, and a 2800-mesh filter is used for filtration and the filtration is allowed to stand for (3-5) h to obtain the aramid nanofiber wet gel.
[0031] Then, (5-10) g / L of polyvinyl alcohol solution is added into the aramid nanofiber wet gel in a ratio of (5-10) mL: (20-30) g to prepare the aramid nanofiber coating.
[0032] Step 3: Mix the mica flakes and the aramid nanofiber coating in a ratio of (85-95) g: (5-15) g (stirring rotation number is (10000-20000) revolutions), scrape and apply into a (1-2) mm aramid mica thin layer, and dry at (80-105) ° C for (10-20) min to obtain a dried aramid mica thin layer;
[0033] Step 4: Add aramid nanofiber coating at (15-25) g / m 2 The coating amount is sprayed on the surface of the glass fiber cloth, and then the surface coated with aramid nanofibers is contacted with a dried aramid mica thin layer, and hot-pressed and bonded at (150-200)°C and (5-10)MPa to obtain an aramid nanofiber reinforced cable core tape material. Figure 1 The structure of the cable core wrapping material is, from top to bottom, an aramid mica thin layer mixed with aramid nanofibers and mica flakes, aramid nanofibers and glass fiber cloth.
[0034] The invention also discloses a cable core tape material prepared by the method for preparing the aramid nanofiber reinforced cable core tape material.
[0035] Example 1
[0036] An aramid nanofiber reinforced cable core tape material and a preparation method thereof, comprising the following steps:
[0037] Step 1, preparing potassium hydroxide into an alkali solution with a concentration of (1.0-1.2) g / mL;
[0038] Step 2, adding alkali solution, dimethyl sulfoxide, and aramid fiber into a stirrer in the ratio of 2 mL: 400 mL: 2 g, stirring and reacting at a speed of 300 r / min for 24 h to obtain an aramid nanofiber dispersion;
[0039] Step 3, adding deionized water to the aramid nanofiber dispersion at a ratio of 100:600 mL, stirring at a speed of 300 r / min for 2 h to replace the solvent;
[0040] Step 4: The mixed system obtained by stirring in the previous step was filtered through a 2800-mesh filter for 3 hours to collect the aramid nanofiber gel;
[0041] Step 5: prepare a 5 g / L polyvinyl alcohol solution, and add the polyvinyl alcohol solution to the aramid nanofiber wet gel at a ratio of 5 mL:20 g;
[0042] Step 6: Add mica to the aramid nanofiber coating in a ratio of 85g:5g, stir evenly at 10,000 rpm, and scrape to form a 1mm thick aramid mica thin layer;
[0043] Step 7: Transfer the thin layer to a paper sheet dryer and heat dry it at 80°C for 20 minutes to obtain an aramid mica thin layer;
[0044] Step 8: Spray 15g / m2 on the surface of the glass fiber cloth 2 The aramid nanofiber coating is then bonded to the aramid mica thin layer obtained in the previous step and the glass fiber cloth by hot pressing at a temperature of 150°C and a pressure of 5 MPa for 10 minutes.
[0045] The cable core tape prepared in Example 1 has a dielectric strength of 38.4 kV / mm, a limiting oxygen index of 48%, a tensile strength of 85.7 N / cm, and a volume resistivity of 9.4×10 13 Ω·m, temperature resistance grade C (above 180℃), is an aramid nanofiber reinforced cable core tape material.
[0046] Example 2
[0047] Step 1, preparing an alkali solution with a concentration of 1.1 g / mL by mixing potassium hydroxide and lithium hydroxide;
[0048] Step 2, adding alkali solution, dimethyl sulfoxide, and aramid fiber into a stirrer in the ratio of 3 mL: 500 mL: 4 g, stirring and reacting at a speed of 600 r / min for 48 hours to obtain an aramid nanofiber dispersion;
[0049] Step 3, adding deionized water to the aramid nanofiber dispersion at a ratio of 200:600 mL, stirring at a speed of 600 r / min for 4 h to replace the solvent;
[0050] Step 4: The mixed system obtained by stirring in the previous step was filtered through a 2800-mesh filter for 5 hours to collect the aramid nanofiber gel;
[0051] Step 5: prepare a 10 g / L polyvinyl alcohol solution, and add the polyvinyl alcohol solution to the aramid nanofiber wet gel at a ratio of 10 mL:30 g;
[0052] Step 6: Add mica to the aramid nanofiber coating in a ratio of 95g:15g, stir evenly at 20,000 rpm, and scrape to form a 2mm thick aramid mica thin layer;
[0053] Step 7: Transfer the thin layer to a paper sheet dryer and heat dry it at 105°C for 10 minutes to obtain an aramid mica thin layer;
[0054] Step 8: Spray 20g / m2 on the surface of the glass fiber cloth 2 The aramid nanofiber coating is then bonded to the aramid mica thin layer obtained in the previous step and the glass fiber cloth under hot pressing temperature of 200°C and pressure of 10 MPa for 5 minutes.
[0055] The cable core tape prepared in Example 2 has a dielectric strength of 37.9 kv / mm, a limiting oxygen index of 45%, a tensile strength of 79.6 N / cm, and a volume resistivity of 8.8×10 14 Ω·m, temperature resistance grade C (above 180℃), is an aramid nanofiber reinforced cable core tape material.
[0056] Example 3
[0057] Step 1, preparing an alkali solution with a concentration of 1.2 g / mL by using potassium hydroxide and potassium tert-butoxide;
[0058] Step 2, adding alkali solution, dimethyl sulfoxide, and aramid fiber into a stirrer in the ratio of 3 mL: 400 mL: 3 g, stirring and reacting at a speed of 500 r / min for 36 hours to obtain an aramid nanofiber dispersion;
[0059] Step 3, adding deionized water to the aramid nanofiber dispersion at a ratio of 200:800 mL, stirring at a speed of 600 r / min for 4 hours to replace the solvent;
[0060] Step 4: The mixed system obtained by stirring in the previous step was filtered through a 2800-mesh filter for 4 hours to collect the aramid nanofiber gel;
[0061] Step 5: prepare a 10 g / L polyvinyl alcohol solution, and add the polyvinyl alcohol solution to the aramid nanofiber wet gel at a ratio of 10 mL:30 g;
[0062] Step 6: Add mica to the aramid nanofiber coating in a ratio of 90g:10g, stir evenly at 15,000 rpm, and scrape to form a 2mm thick aramid mica thin layer;
[0063] Step 7: Transfer the thin layer to a paper sheet dryer and heat dry it at 100°C for 12 minutes to obtain an aramid mica thin layer;
[0064] Step 8: Spray 20g / m2 on the surface of the glass fiber cloth 2 The aramid nanofiber coating is then bonded to the aramid mica thin layer obtained in the previous step and the glass fiber cloth by hot pressing at a temperature of 180°C and a pressure of 8 MPa for 7 minutes.
[0065] The cable core tape prepared in Example 3 has a dielectric strength of 42.3 kv / mm, a limiting oxygen index of 47%, a tensile strength of 86.3 N / cm, and a volume resistivity of 8.5×10 15 Ω·m, temperature resistance grade C (above 180℃), is an aramid nanofiber reinforced cable core tape material.
[0066] Example 4
[0067] Step 1, preparing potassium hydroxide into an alkali solution with a concentration of 1.2 g / mL;
[0068] Step 2, adding alkali solution, dimethyl sulfoxide, and aramid fiber into a stirrer in the ratio of 3 mL: 400 mL: 3 g, stirring and reacting at a speed of 500 r / min for 36 hours to obtain an aramid nanofiber dispersion;
[0069] Step 3, adding deionized water to the aramid nanofiber dispersion at a ratio of 150:800 mL, stirring at a speed of 400 r / min for 3 h to perform solvent replacement;
[0070] Step 4: The mixed system obtained by stirring in the previous step was filtered through a 2800-mesh filter for 4 hours to collect the aramid nanofiber gel;
[0071] Step 5: prepare a 5 g / L polyvinyl alcohol solution, and add the polyvinyl alcohol solution to the aramid nanofiber wet gel at a ratio of 5 mL:20 g;
[0072] Step 6: Add mica to the aramid nanofiber coating in a ratio of 90 g:15 g, stir evenly at 20,000 rpm, and scrape to form a 1.5 mm thick aramid mica thin layer;
[0073] Step 7: Transfer the thin layer to a paper sheet dryer and heat dry it at 90°C for 14 minutes to obtain an aramid mica thin layer;
[0074] Step 8: Spray 25g / m2 on the surface of the glass fiber cloth 2 The aramid nanofiber coating is then bonded to the aramid mica thin layer obtained in the previous step and the glass fiber cloth by hot pressing at a temperature of 200°C and a pressure of 7 MPa for 9 minutes.
[0075] The cable core tape prepared in Example 4 has a dielectric strength of 41.5 kV / mm, a limiting oxygen index of 47%, a tensile strength of 90.1 N / cm, and a volume resistivity of 7.3×10 14 Ω·m, temperature resistance grade C (above 180℃), is an aramid nanofiber reinforced cable core tape material.
[0076] Example 5
[0077] Step 1, preparing an alkali solution with a concentration of 1.0 g / mL by mixing potassium hydroxide, potassium tert-butoxide and lithium hydroxide;
[0078] Step 2, adding alkali solution, dimethyl sulfoxide, and aramid fiber into a stirrer in the ratio of 3 mL: 500 mL: 4 g, stirring and reacting at a speed of 600 r / min for 48 hours to obtain an aramid nanofiber dispersion;
[0079] Step 3, adding deionized water to the aramid nanofiber dispersion at a ratio of 200:600 mL, stirring at a speed of 400 r / min for 4 hours to replace the solvent;
[0080] Step 4: The mixed system obtained by stirring in the previous step was filtered through a 2800-mesh filter for 5 hours to collect the aramid nanofiber gel;
[0081] Step 5: prepare a 10 g / L polyvinyl alcohol solution, and add the polyvinyl alcohol solution to the aramid nanofiber wet gel at a ratio of 5 mL:30 g;
[0082] Step 6: Add mica to the aramid nanofiber coating in a ratio of 95g:5g, stir evenly at 20,000 rpm, and scrape to form a 2mm thick aramid mica thin layer;
[0083] Step 7: Transfer the thin layer to a paper sheet dryer and heat dry it at 85°C for 15 minutes to obtain an aramid mica thin layer;
[0084] Step 8: Spray 25g / m2 on the surface of the glass fiber cloth 2 The aramid nanofiber coating is then bonded to the aramid mica thin layer obtained in the previous step and the glass fiber cloth by hot pressing at a temperature of 170°C and a pressure of 8 MPa for 9 minutes.
[0085] The cable core tape prepared in Example 5 has a dielectric strength of 42.6 kv / mm, a limiting oxygen index of 48%, a tensile strength of 83.5 N / cm, and a volume resistivity of 8.2×10 14 Ω·m, temperature resistance grade C (above 180℃), is an aramid nanofiber reinforced cable core tape material.
[0086] Table 1 Technical parameters of cable core wrapping tape for implementation cases
[0087]
[0088] Table 1 shows the technical parameters of the cable core tape prepared in the embodiment. It can be analyzed that the cable core tape material prepared by the process provided by the present invention has high dielectric strength, all exceeding 37 kV / mm%, good mechanical strength, tensile strength exceeding 79 N / cm, excellent insulation performance, and volume resistance greater than 10 13 Ω·m, can withstand high temperature above 180℃.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.
Claims
1. A method for preparing an aramid nanofiber reinforced cable core tape material, characterized in that: The steps include: Step 1, adding highly concentrated alkali solution, dimethyl sulfoxide and aramid fiber in sequence, and then sealing and stirring to react to prepare a dark red aramid nanofiber dispersion; Step 2, adding deionized water to the aramid nanofiber dispersion to perform solvent replacement by stirring, and filtering to obtain an aramid nanofiber wet gel; then adding a polyvinyl alcohol solution to the aramid nanofiber wet gel to prepare an aramid nanofiber coating; Step 3: Evenly mix the mica flakes and the aramid nanofiber coating, apply them by scraping to form an aramid mica thin layer, and dry them to obtain a dried aramid mica thin layer; Step 4: Spray the aramid nanofiber coating on the surface of the glass fiber cloth, and then bring the surface coated with the aramid nanofiber into contact with the dried aramid mica thin layer for hot pressing and bonding to obtain the aramid nanofiber reinforced cable core wrapping material.
2. The method for preparing an aramid nanofiber reinforced cable core tape material according to claim 1, characterized in that: In step 1, the aramid fiber is a para-aramid fiber with a para-structure of (1414), and the raw materials of the aramid fiber are para-aramid short chopped fibers, para-aramid fiber fabrics, para-aramid fiber scraps, and high-temperature resistant protective gear woven with para-aramid fibers.
3. The method for preparing an aramid nanofiber reinforced cable core tape material according to claim 1, characterized in that: In step 1, the ratio of high-concentration alkali solution, dimethyl sulfoxide, and aramid fiber is (2-3) mL: (400-500) mL: (2-4) g, wherein the alkali solution is a combination or any one of potassium tert-butoxide, potassium hydroxide, and lithium hydroxide, with a concentration of (1.0-1.2) g / mL, the stirring reaction time is (24-48) h, and the rotation speed is (300-600) r / min.
4. The method for preparing an aramid nanofiber reinforced cable core tape material according to claim 1, characterized in that: In step 2, the ratio of deionized water to aramid nanofiber dispersion is (100-200) mL: (600-800) mL, wherein the stirring time is (2-4) h, the rotation speed is (300-400) r / min, and a 2800-mesh filter is used for filtration and the filtration is allowed to stand for (3-5) h.
5. The method for preparing an aramid nanofiber reinforced cable core tape material according to claim 1, characterized in that: In step 2, the polyvinyl alcohol solution is (5-10) g / L; the polyvinyl alcohol solution is added to the aramid nanofiber wet gel in a ratio of (5-10) mL: (20-30) g.
6. The method for preparing an aramid nanofiber reinforced cable core tape material according to claim 1, characterized in that: In step 3, during mixing, the mica flakes and the aramid coating are mixed in a ratio of (85-95) g: (5-15) g, and the mixing is evenly stirred at a number of (10000-20000) revolutions.
7. The method for preparing an aramid nanofiber reinforced cable core tape material according to claim 1, characterized in that: In step 3, the thickness of the aramid mica thin layer is (1-2) mm.
8. The method for preparing an aramid nanofiber reinforced cable core tape material according to claim 1, characterized in that: In step 3, the temperature during drying is (80-105)°C and the time is (10-20) min.
9. The method for preparing an aramid nanofiber reinforced cable core tape material according to claim 1, characterized in that: In step 4, the spraying amount of the aramid nanofiber coating on the surface of the glass fiber cloth is (15-25) g / m 2 The temperature during hot pressing is (150-200)°C and the pressure is (5-10) MPa.
10. A cable core tape material prepared by the method for preparing an aramid nanofiber reinforced cable core tape material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Mica paper and production method
CN103880326A
Aramid nanofiber / polyvinyl alcohol / polyaniline composite hydrogel and preparation method and application thereof
CN110776654A